Resilience in women with autoimmune rheumatic diseases (2018)
Objective: To evaluate the relationship between resilience and clinical outcomes in patients with autoimmune rheumatic diseases. Methods: Focus groups, individual interviews, and chart reviews were done to collect data on 188 women with autoimmune rheumatic diseases, namely rheumatoid arthritis (n = 51), systemic lupus erythematosus (n = 70), systemic sclerosis (n = 35), and Sjögren's syndrome (n = 32). Demographic, clinical, and laboratory variables were assessed including disease activity by patient reported outcomes. Resilience was evaluated by using the Brief Resilience Scale. Bivariate, multiple linear regression, and classification and regression trees were used to analyse data. Results: Resilience was influenced by age, duration of disease, and socioeconomic status. Lower resilience scores were observed in younger patients ( less than 48 years) with systemic lupus erythematosus, rheumatoid arthritis, and systemic sclerosis who had low socioeconomic status, whereas older patients (> 50 years) had higher resilience scores regardless of socioeconomic status. There was no influence of disease activity on resilience. A particular behaviour was observed in systemic sclerosis in which patients with high socioeconomic status and regular physical activity had higher resilience scores. Conclusion: Resilience in patients with autoimmune rheumatic diseases is a continuum process influenced by age and socioeconomic status. The ways in which these variables along with exercise influence resilience deserve further investigation. © 2017 Société française de rhumatologie